PERAN PEMIMPIN DALAM MENINGKATKAN KINERJA ORGANISASI DI ERA TEKNOLOGI DIGITAL PADA HOTEL SUDAMALA RESORT – LABUAN BAJO - Iwan Iswanto, Andy (AKSIOMA : Jurnal Manajemen, 2023)
The purpose of this research is to find out the role of the leader in the era of digital technology at the Sudamala Resort Komodo hotel, Labuan Bajo and how the impact of the role of the leader has on improving organizational performance. This research uses a qualitative research design by conducting interviews with the General Manager at the Sudamala Resort Hotel and the Human Resources Manager, also collecting data with documents owned by the company. The results of this research are that the role of the leader greatly impacts on improving the performance of organizational members. Especially in the era of digital technology like today, the role of a leader is very important. Leaders with strong character, with the ability to lead by example, provide positive energy through a motivating presence, and become partners for team members, have a positive impact on the organization. The team members become more with integrity and responsibility. This atmosphere makes an organization in any situation, including in the development of digital technology, all members of the organization have resilience, are always innovative and creative, also work together to advance the organization.